2021
DOI: 10.1021/acs.nanolett.0c04652
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Nanosecond Operation in Stochastic Magnetic Tunnel Junctions

Abstract: Magnetic tunnel junctions operating in the superparamagnetic regime are promising devices in the field of probabilistic computing, which is suitable for applications like high-dimensional optimization or sampling problems. Further, random number generation is of interest in the field of cryptography. For such applications, a device’s uncorrelated fluctuation time-scale can determine the effective system speed. It has been theoretically proposed that a magnetic tunnel junction designed to have only easy-plane a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…While this figure is not precise, it indicates the potential for ultra-low-energy consumption. Furthermore, Safranski et al 34 have verified that uncorrelated thermally-driven switching can be observed in CoFeB MTJs for dwell times of 5 ns and above, which we can take as a floor for the operational speed of these nanodots. Longer dwell times can easily be induced by scaling up the size of the magnetic elements, thus increas-ing the energy barrier between states.…”
mentioning
confidence: 54%
“…While this figure is not precise, it indicates the potential for ultra-low-energy consumption. Furthermore, Safranski et al 34 have verified that uncorrelated thermally-driven switching can be observed in CoFeB MTJs for dwell times of 5 ns and above, which we can take as a floor for the operational speed of these nanodots. Longer dwell times can easily be induced by scaling up the size of the magnetic elements, thus increas-ing the energy barrier between states.…”
mentioning
confidence: 54%
“…It is placed in series with a transistor, and the drain voltage is thresholded by an inverter 3 to obtain a random binary output bit whose average value can be tuned through the gate voltage V IN . It has been shown both theoretically 24,25 and experimentally 26,27 that s-MTJ-based p-bits can be designed to generate new random numbers in times ∼ nanoseconds. The same circuit could also be used with other fluctuating resistors 28 , but one advantage of s-MTJ's is that they can be built by modifying magnetoresistive random access memory (MRAM) technology that has already reached gigabit levels of integration 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The overall power consumption of one hardware p-bit is around 20µW which is orders of magnitude better than CMOS alternatives 10 . Another advantage of this compact RNG-source is that it is based on stochastic MTJs which can operate at nanosecond speeds which has been shown theoretically as well as experimentally [16][17][18][19] . The random number generation of the p-bit design can be tuned with the input voltage at the gate of the NMOS-transistor V IN and has a bipolar output voltage V OU T = ±V DD /2.…”
Section: Architecture Of the Probabilistic Coprocessormentioning
confidence: 99%